Magnetic parameters in paleolimnological studies in Antarctica (Latin American Journal of Sedimentology and Basin Analysis, 2021)
Environmental magnetism and paleomagnetism methods are useful tools for climate-related and environmental changes studies, as well as for age dating. In particular, they may be applied in magnetic monitoring and to investigate the behavior, response, and history of environments like rivers, lakes, soils, etc. Although the usefulness of magnetic susceptibility in such applications is well known, in this contribution the potential and the need of using additional parameters obtained from measurements of remanent magnetization (natural, anhysteretic, isothermal), magnetic hysteresis and thermomagnetic studies are discussed. Magnetic signals from sediments and soils are often dominated by ferromagnetic minerals sensu lato: ferrimagnetic (titano)-magnetite and/ or antiferromagnetic hematite. These minerals are often not detected with standard analytical techniques due to their low concentrations (
Keywords: Lakes, Paleomagnetism, AntarcticPeninsula, MagneticProxies